Effects of metformin treatment against endometrial cancer cells cultured in vitro or grafted into female balb/C nude mice: insights into cell response and IGF-1R and PI3K/AKT/mTOR signaling pathways - Santos Fortes dos Reis, Vânia Marisia; Ramos, Franciely Machado; de Oliveira, Henrique Leal; Machado, Fernanda Dapper; Hartke, Sara; Machado-Weber, Amanda; Germeyer, Ariane; Strowitzki, Thomas; Kliemann, Lúcia Maria; von Eye Corleta, Helena; Brum, Ilma Simoni; Capp, Edison; et al. (Cell biochemistry and biophysics, 2025)
Obesity and type II diabetes are independent risk factors for Endometrial cancer (EC) development. Elevated levels of insulin-like growth factor-1 (IGF-1), insulin resistance, and the increased activity of IGF-1 receptor is linked to EC development through the PI3K/AKT/mTOR pathway. The antidiabetic agent metformin is a promising repurposing drug for cancer treatment, but the mechanisms underlying its effects are not completely known. This study evaluated how metformin could act against the EC cell line Ishikawa cultured in vitro or grafted into female Balb/C nude mice. In vitro experiments demonstrated that treatment with 25 mM of metformin reduced cell viability through promoting cytotoxicity, mitochondrial dysfunction, apoptosis, and cell cycle arrest (G1 phase). Mice treatment with 250 mg/kg of metformin for 28 days did not change serum IGF-1 levels nor decreased the grafted cell-induced tumor weight and cell proliferation, but prevented its volume growth while genes of the IGF1-R and PI3K/AKT/mTOR pathways (AKT2, GAPDH, FOXO3, IGF1R, INSR, MAPK3, MTOR, and SHC1) were downregulated. Metformin treatment was more impacting for the in vitro model, but our molecular results provide valuable insights into the possible action of metformin against EC tumoral cells at physiological level. In-silico analysis using Cytoscape indicated that metformin was not described as interacting with AKT2 and SHC1 proteins. Besides interacting with metformin, mTOR and MAPK3 present the larger number of interactions with the other proteins. These four genes/proteins emerge as potential targets for deepening studies to determine the metformin’s role in longer EC treatment using animal models.